Individual Pay and Outside Options: Evidence from the Polish Labour Force Survey - Fiona Duffy; Patrick Paul Walsh (Institute for the Study of Labor (IZA), 2001)
Using Polish Labour Force Survey data, we examine whether competition for labour has induced individual pay to depend on outside options, availability and quality of jobs. Exploiting the lack of inter-regional job and worker flows we estimate the elasticity of individual pay, amongst a rich set of individual characteristics, to be approximately -0.1 for local unemployment (job shortages) and + 0.1 for local job reallocation (restructuring). Variations in local labour market conditions explain approximately 50 per cent of the differences in expected individual earnings across regions, while differences in inherited human capital and occupation structures explain the rest.
Keywords: O5; J6; L0; 330; Wage determination; unemployment; job reallocation and polish regions; Lohn; Regionale Lohnstruktur; Regionale Arbeitslosigkeit; Humankapital; Sektorale Beschäftigungsstruktur; Arbeitsmobilität; Schätzung; Polen